The Geography of Territorial Capital in the European Union: a Map and Several Policy Issues - Valentin Cojanu; Raluca Robu (Transylvanian Review of Administrative Sciences, 2019)
This paper investigates the territorial capital endowments across European regions. Data are collected at NUTS 2 level for all European regions, for the most recent year available, for several indicators that measure different components of territorial capital. Our evidence reveals several patterns of regional economic development, with specific configurations of the territorial assets, which further shed light on the connection between location, competitiveness and development.